Volume 2A: Turbomachinery 2014
DOI: 10.1115/gt2014-26345
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Analysis of Radial Clearance Influence on Rotor and Stator Clocking Effect by Example of Model High Loaded Two Stage Compressor

Abstract: It is ascertained that optimization of bladed rows clocking positions is an effective tool for control of bladed rows unsteady interaction in a multistage turbo machine and could be used equally in refinement and in compressor design stages [1–3]. Up to now the clocking effect issue of highly loaded rotors in compressor stages was not investigated due to growing design complexity of the experimental facility. The issue concerning tip clearances value influence on rotor and stator clocking effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…The circumferential phase difference between adjacent stators or rotors in turbomachines causes the mixing loss and energy change variation, intensifying the unsteady characteristics of the flow field. This phenomenon was named the clocking effect in previous studies [45][46][47][48].…”
Section: Turbine Flows With Clocking Effectmentioning
confidence: 90%
“…The circumferential phase difference between adjacent stators or rotors in turbomachines causes the mixing loss and energy change variation, intensifying the unsteady characteristics of the flow field. This phenomenon was named the clocking effect in previous studies [45][46][47][48].…”
Section: Turbine Flows With Clocking Effectmentioning
confidence: 90%
“…Mileshin et al [18] showed that the clocking effect becomes weaker as the tip clearance increases, and [19] demonstrated that the clocking effect becomes stronger as the Reynolds number decreases. Layachi and Bölcs [20] experimentally studied the influence of axial spacing variation on the clocking effect.…”
Section: Introductionmentioning
confidence: 99%
“…Для парирования негативного влияния радиального зазора на внутреннюю поверхность корпуса КВД наносится легко срабатываемое покрытие. Однако в процессе эксплуатации КВД из-за наличия переходных нестационарных режимов, овализации корпусов, входной неравномерности потока происходит выработка покрытия корпусов, которая приводит к увеличению величины радиального зазора и к дальнейшему ухудшению характеристик КВД [6][7][8].…”
Section: Introductionunclassified